THE INFLUENCE OF THE FAMILY ENVIRONMENT ON THE CHILD'S SELF-ESTEEM - Avazbekova Umidabonu Farxod qizi (Ecominds Press, 2025)
The article presents views on the influence of the family environment on the characteristic, positive and negative effects on the upbringing of children, as well as on self-esteem.
Keywords: Family, upbringing, child, status, rule, signal, parent, self, norm, family upbringing, perception.